Homogeneous and heterogenised masked N-heterocyclic carbenes for bio-based cyclic carbonate synthesis. Issue 6 (9th November 2015) - Stewart, Joseph A.; Drexel, Roland; Arstad, Bjørnar; Reubsaet, Erik; Weckhuysen, Bert M.; Bruijnincx, Pieter C. A.
Abstract : Substrate scope (including crude glycerol), influence of organocatalyst structure, mechanistic aspects and catalyst heterogenisation are reported. Abstract : (Multifunctional) cyclic carbonates are generating much interest, with bio-based bis-cyclic compounds attracting attention from the polymer sector as potential renewable monomers for systems such as non-isocyanate polyurethanes. Here, the efficient synthesis of one such substrate, diglycerol dicarbonate, utilising CO2 -masked N-heterocyclic carbene (NHC) organocatalysts is demonstrated. The 1, 3-dialkylimidazole-2-carboxylate pre-catalyst, which can be produced both in and ex situ, yields the desired cyclic product, expressing full conversion within 3 h when using the ex situ synthesised pre-catalyst with 5 mol% loading, but can also operate with 1 mol% loading efficiently. Substituted derivatives of the imidazole-based organocatalyst have also been investigated to gauge the sensitivity of the system. A number of bio-based diols are also investigated, with 1, 2-, 2, 3- and 1, 3-diols yielding five- and six-membered cyclic products, respectively; 1, 3-diols are significantly more reluctant to cyclisation, yielding both 1- and 3-monocarbonates, dicarbonates and the cyclic products. A more in depth study was also carried out on glycerol as a substrate, both in its pure a crude form, providing insight into how impurities impact on the activity of the carbene catalyst. Through 13 C-labelled reagent experiments, a mechanism is proposed for the conversion of diols to their cyclic carbonate analogues. Finally, the organocatalyst was immobilized on siliceous mesostructured cellular foam (MCF). Using an alternative activation procedure, a supported, masked NHC catalyst is achieved and characterised with DRIFTS, TGA and 13 C solid-state NMR. This heterogenised catalyst can be easily recovered and reused up to three times expressing its original activity if properly regenerated by a simple ion exchange procedure. Of important note, this system can also successfully convert crude glycerol with high selectivity observed for the cyclic product.